Between prudence and innovation: A critical analysis of the Indonesian Ulema Council fatwa on Bitcoin in Islamic finance - Zamrud, Ahmad Khalifah; Jafar, Usman; Haddade, Abdul Wahid (Journal of Islamic Economics Lariba, 2026)
IntroductionThe rapid expansion of cryptocurrency has generated significant debate within Islamic economic discourse. Bitcoin, as the first decentralized digital currency, offers technological advantages such as transparency, efficiency, and global accessibility. However, it also raises concerns regarding price volatility, speculative trading behavior, and the absence of intrinsic value. These issues have prompted Islamic scholars and regulatory institutions to evaluate cryptocurrency from the perspective of Islamic law and financial ethics. In Indonesia, the Indonesian Ulema Council issued a religious ruling declaring Bitcoin impermissible due to elements of uncertainty, speculation, and potential economic harm. This ruling has stimulated ongoing discussion about the compatibility of cryptocurrency innovation with Islamic economic principles.ObjectivesThis study aims to critically analyze the religious ruling on Bitcoin issued by the Indonesian Ulema Council by examining its legal reasoning, its relationship with Islamic economic principles, and its implications for the governance of digital financial innovation. The research also seeks to explore whether cryptocurrency can be accommodated within an Islamic economic framework under certain regulatory and ethical conditions.MethodThe study employs a qualitative research design using a transdisciplinary analytical approach that integrates perspectives from Islamic jurisprudence, Islamic economics, financial regulation, and digital financial technology. Data were collected through documentation of religious rulings, regulatory policies, and scholarly literature related to cryptocurrency and Islamic finance. The data were analyzed through thematic and comparative analysis to identify the legal reasoning underlying the prohibition of Bitcoin and to evaluate alternative scholarly interpretations regarding the status of digital assets in Islamic economics.ResultsThe findings indicate that the prohibition of Bitcoin is primarily based on concerns about excessive uncertainty, speculative trading behavior, and potential economic harm associated with cryptocurrency markets. Nevertheless, the analysis also reveals that cryptocurrency may be considered permissible when these elements are mitigated through transparent governance, regulatory oversight, and the development of asset-backed digital financial instruments.ImplicationsThe study highlights the importance of developing regulatory and institutional frameworks that reconcile financial innovation with Islamic ethical principles. Such frameworks can provide clearer guidance for Muslim investors while supporting responsible digital financial development.Originality or NoveltyThis research contributes to the growing literature on cryptocurrency in Islamic economics by offering a critical analysis of religious rulings within the broader context of digital financial transformation and regulatory governance.